Pengaruh Gaya Kepemimpinan Transformasional dan Transaksional Terhadap Kinerja Karyawan Produksi di PT New Asia international - Bibit Bagus Elfrianto Putra; Dwiarko Nugrohoseno (Universitas Negeri Surabaya, 2026)
This study investigates the influence of transformational and transactional leadership styles on the performance of production employees. The study is motivated by the importance of effective leadership in improving employee performance, particularly in manufacturing environments where productivity and coordination play a crucial role in achieving organizational targets. Leadership style is considered one of the key factors that can influence employee motivation, work behavior, and overall performance in production settings. Therefore, understanding the relationship between leadership approaches and employee performance becomes essential for organizational effectiveness. This research employs a quantitative method using multiple linear regression analysis to examine the relationship between transformational and transactional leadership styles and employee performance. The sample consists of 82 production employees selected through purposive sampling to ensure that respondents meet the research criteria. Data were collected through structured questionnaires distributed to the respondents. The results of the analysis indicate that neither transformational leadership nor transactional leadership has a significant effect on employee performance, either partially or simultaneously. These findings suggest that the leadership approaches applied may not fully align with the characteristics, expectations, or working conditions of production employees. Consequently, organizations are encouraged to evaluate and adjust their leadership strategies to better match employee needs and workplace dynamics. Such adjustments are expected to help optimize employee performance and improve organizational effectiveness, particularly in production-oriented work environments.